2014
DOI: 10.1051/0004-6361/201424348
|View full text |Cite
|
Sign up to set email alerts
|

The nature of separator current layers in MHS equilibria

Abstract: Context. Separators, which are in many ways the three-dimensional equivalent to two-dimensional nulls, are important sites for magnetic reconnection. Magnetic reconnection occurs in strong current layers which have very short length scales. Aims. The aim of this work is to explore the nature of current layers around separators. A separator is a special field line which lies along the intersection of two separatrix surfaces and forms the boundary between four topologically distinct flux domains. In particular, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…It is known that separators are prone to current sheet formation (Lau & Finn 1990;Parnell et al 2010b;Stevenson et al 2015) and thus are likely sites of magnetic reconnection. Theoretical studies of separator reconnection have continued to evolve over many years (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that separators are prone to current sheet formation (Lau & Finn 1990;Parnell et al 2010b;Stevenson et al 2015) and thus are likely sites of magnetic reconnection. Theoretical studies of separator reconnection have continued to evolve over many years (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A separator lies on the boundary of four topologically distinct flux domains (i.e., movement between the domains would result in a discontinuous jump in field line mapping), and so field lines in the vicinity of separators are sensitive to flows across these boundaries. Hence, currents build easily along separators [ Lau and Finn , ; Haynes et al , ; Parnell et al , , ; Stevenson et al , ], and so they are prime locations where 3‐D reconnection occurs.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we detail the properties of 3‐D separator reconnection in a nondriven experiment, to avoid any such problems, and also where the null points and separator are far from the boundary. The model starts from a MHS equilibrium, containing a separator current layer and excess energy above that of a potential field, formed through the nonresistive relaxation of an initially nonpotential, non–force‐free field, discussed in detail in Stevenson et al []. Reconnection is triggered at the separator current layer using an anomalous diffusivity to mimic the onset of microinstabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lau & Finn 1990;Priest et al 2003;Baumann et al 2013;Parnell et al 2010Parnell et al , 2015Stevenson et al 2015) examining the importance of topological features, such as separators and null points as locations for current build up and reconnection to occur. However, it has also been shown that geometrical features, such as quasi-separatrix layers (QSLs; Priest & Démoulin 1995;Démoulin et al 1996a,b), where the A&A 594, A67 (2016) change in connectivity is continuous but very large, are also locations associated with current formation and energy release (e.g.…”
Section: Introductionmentioning
confidence: 99%